PERPUSTAKAAN STIHPADA DARI SUDUT GEDUNG HINGGA MENJADI RUANG NYAMAN DAN INOVATIF - Putri, Tara Selvianti; Wahidi, Ahmad (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The background of this research is to understand the strategy of managing a library that has dual functions, namely as a place of education and recreation, in the context of STIHPADA Library. The research method is descriptive qualitative method, the main method is interview with qualitative approach, documentation method to support data collection. The documentation includes taking photos, videos, audio recordings, and literature review which includes references from relevant journals. The use of various data sources is expected to provide more detailed and comprehensive information related to the research topic. The data collected is then explained narratively, using words to convey the meaning and interpretation of the findings. With this approach, it is hoped that this article will be able to provide an in-depth and accurate understanding of the subject under study, as well as present useful information for the development of literature and research in related fields. The results showed that Innovation in Services where the application of modern technology in the library, for example the use of digital systems for borrowing books, e-book access, or application-based services that facilitate visitors.